2012
DOI: 10.1177/0194599812458771
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Repetitive Transcranial Magnetic Stimulation for Chronic Tinnitus

Abstract: Repetitive transcranial magnetic stimulation could be a new therapeutic tool for the treatment of chronic tinnitus, and thus far we have not been able to demonstrate any substantial risk from rTMS treatment. However, the long-term effects of rTMS treatment for tinnitus are not clear and will require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 44 publications
3
30
1
4
Order By: Relevance
“…Repetitive transcranial magnetic stimulation (rTMS) is one, although its benefits currently remain elusive (Folmer et al, 2006; Peng et al, 2012). Other innovative treatments will undoubtedly appear in the area of acoustic therapy as discoveries are made with respect to the long-term effects of sound on the tinnitus percept.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is one, although its benefits currently remain elusive (Folmer et al, 2006; Peng et al, 2012). Other innovative treatments will undoubtedly appear in the area of acoustic therapy as discoveries are made with respect to the long-term effects of sound on the tinnitus percept.…”
Section: Discussionmentioning
confidence: 99%
“…rTMS is a novel therapeutic tool targeting hyperactivity/abnormal synchronization within the auditory cortex associated with a variety of psychological and neurological conditions [15]. It is essential to develop a method whereby tinnitus may be reliably and validly quantitated, clinically meaningful changes in tinnitus detected, and treatment outcomes assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese review article found 5 randomized controlled studies with a total of 160 patients but only short follow-up intervals. The authors conclude that long-term effects cannot be determined reliably [103]. An article from Boston assessed 105 publications with a total of 1,815 patients with special attention to side effects.…”
Section: Neuromodulation – Instrument-based Medical Interventionsmentioning
confidence: 99%